APLIKASI TEKNOLOGI MICROBIAL FUEL CELL (MFC) UNTUK MENENTUKAN ENERGI LISTRIK SUBSTRAT BATANG SAGU (METROXYLON) - Rahmaniah Rahmaniah; Suriana Binti Ardi; Nurul Fuadi (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2020)
This study aims to determine how much electrical energy or power density produced from the sago stem substrate using Microbial Fuel Cell (MFC) technology without the addition of electrolytes by adding KMnO4 and K3Fe (CN) 6 as an electrolyte solution. From the measurement results, it is obtained that the sago stem substrate sample has electrical potential or power density (mW/m2). The large power density (mW/m2) produced from the sago stem substrate using lactobacillus plantarum bacteria without the addition of an electrolyte solution was obtained at 50,082 mW/m2. For samples with the addition of 0.2 M KMnO4 and potassium phosphate buffer with pH 7, a power density value of 91,082 mW/m2 was obtained and the addition of K3Fe (CN) 6 0.2 M and sodium phosphate buffer with pH 7 obtained a power density value of 27,287 mW/m2.